Purposeful Use of Digital and Artificial Intelligence Technologies in Improving the Quality of Education in the Higher Education System - Xudazarov, Ravshan (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
Digital technologies are gaining significant importance in all sectors worldwide. Every aspect of our lives, our communication with others, professional activities, as well as the processes of learning and teaching, now require the use of computers from the very first steps.In this article, important information is provided regarding the necessity of actively utilizing computers and artificial intelligence technologies in educational activities within the higher education system. Today, providing students of the digital generation with visually rich and creative-thinking-stimulating materials during classes has become widely promoted and encouraged.